2016
DOI: 10.1016/j.chemosphere.2015.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of tris (1-chloro-2-propyl) phosphate (TCIPP) metabolism in human liver microsomes and serum

Abstract: Tris(1-chloro-2-propyl) phosphate (TCIPP) is an emerging contaminant which is ubiquitous in the indoor and outdoor environment. Moreover, its presence in human body fluids and biota has been evidenced. Since no quantitative data exist on the biotransformation or stability of TCIPP in the human body, we performed an in vitro incubation of TCIPP with human liver microsomes (HLM) and human serum (HS). Two metabolites, namely bis(2-chloro-isopropyl) phosphate (BCIPP) and bis(1-chloro-2-propyl) 1-hydroxy-2-propyl p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…For BCIPHIPP, the truncated increase in formation at 100 μM TCIPP suggests that the enzymatic capacity for BCIPHIPP production was reaching saturation, which is in line with its observed K m of 80 μM in human liver microsomes (Van den Eede et al, 2015c).…”
Section: Tris(1-chloro-2-propyl) Phosphatesupporting
confidence: 77%
See 1 more Smart Citation
“…For BCIPHIPP, the truncated increase in formation at 100 μM TCIPP suggests that the enzymatic capacity for BCIPHIPP production was reaching saturation, which is in line with its observed K m of 80 μM in human liver microsomes (Van den Eede et al, 2015c).…”
Section: Tris(1-chloro-2-propyl) Phosphatesupporting
confidence: 77%
“…Remarkably, BCIPP formation in hepatocytes was slightly lower compared to extrapolated human liver microsome data (Table S3), while BCIPHIPP did not show this trend. Possibly, the observed hydrolysis by buffer components in that study influenced the estimated non-linear regression parameters (Van den Eede et al, 2015c).…”
Section: Tris(1-chloro-2-propyl) Phosphatementioning
confidence: 89%
“…The low detection frequency of BCIPP may be due to the formation of other non-dealkylated TCIPP metabolites, namely BCIPHIPP, as suggested by an in vitro study 14 . However, further work by the same research group showed that BCIPHIPP formation was 10-fold lower than BCIPP in human liver microsomes 15 . Thus, the low detection frequency of BCIPP may be due to the higher detection limits.…”
Section: Resultsmentioning
confidence: 95%
“…In vitro studies show that PFRs are readily metabolized to their diester metabolites as well as various phase II conjugate metabolites 14, 15 . Predominately detected diester metabolites include diphenyl phosphate (DPHP) and bis(1,3-dichloro-2propyl) phosphate (BDCIPP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation